Isolation, characterisation and expression of fructose-1, 6-bisphophate aldolase from sago palm (metroxylon sagu) leaves - Jerry, anak Gerunsin (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Starch in sago palm (Metroxylon sagu) has been utilized for many years as an energy source in animal and human. Research in sago palm has been focused on alteration of the machinery that involved in starch production. This plant has been an interesting subject in this study because of its remarkable characteristic that can withstand physiological drought of salinity, prolonged flooding as well as soil acidity and yet still be able to produce a substantial amount of energy reserve. Fructose bisphosphate aldolase (FBA), which is responsible in cleavage of β-fructose-1,6-phosphate to D-glyceraldehyde-3-phosphate and dihydroxyacetone phosphate in reversible reaction of aldol condensation. Abundantly distributed in both photosynthetic and non-photosynthetic tissues, this enzyme plays vital role in glycolysis and gluconeogenesis. A modified RNA extraction method was developed specifically for sago palm leaves in this study. This includes inclusion of PVPP prior to RNA extraction together with PVP40 that was prepared in the extraction buffer. RNA integrity which was assessed quantitatively shows a comparable result. Additionally, a good quality of sago palm RNA where RNA integrity number over 8 (RIN>8) was obtained using the modified method, which can further be used for Next Generation Sequencing (NGS). Method employing 3‟-end Rapid Amplification cDNA Ends (RACE) was used in this study where (dT)17 adapter was employed to elucidate the downstream of sequence. Sequence from the 5‟-end was obtained through variation of classical RACE where a modified degenerated oligo(dT) primer was made to append to the 5‟-end and amplify the upstream of sago palm cDNA via 5‟-RACE. A total of 355 amino acids residue (1070 bp nucleotides) of sago palm fructose bisphosphate aldolase (msFBAld) was isolated using this method. Further investigation reveals that msFBAld belongs to fructose bisphosphate aldolase class I that contains 10 amino acids active sites, with Lycine (K) residue that is essential in participation of aldol condensation and phylogenetic analysis reveals that msFBAld is compartmentalized in plastid. Protein expression on non-denatured SDS-PAGE of recombinant sago palm fructose bisphosphate aldolse (msFBAld) reveals the molecular weight of the recombinant msFBAld with 39 KDa, which is comparable with findings on FBA of other plants. In addition, from the analyzed secondary structure, it is evident that msFBAld obtained from this study have very similar characteristics as other aldolase class I that have been studied from other organisms. In conclusion, this study has successfully isolated, characterized and recombinant msFBAld was expressed in E. coli expression system.